Kuramda ve uygulamada ce - Kaya, Mehti Resul (My University, 1999)
The relationship between Turkey and E.E.C. has taken a new step since January 1st 1996. This step is the period of customs agreement which was already take part within Ankara Treaty. Although the customs agreement is not covering the agricultural sector it is still considered for the reason that agricultural products processed the industrial parts. This study is include general and technical regularity of the sector. At the first part of this study I examined agricultural products and processed agricultural products of EC also all rules and practice of GATT Uruguay Round Agricultural agreement. At the second part of study you can find processed sectors and all rules and technical rules of this sector. At the third part the processed agricultural things according to agreement between Turkey and E.E.C. processed agricultural products has examined from decision of 36. Agricultural products consey. At the fourth part of study you can find all rules for processed agricultural products in Turkey. At the fifth part of this study countries of customs union and all rules and practice has examined. As a result, the import level of processed agricultural products is not serious quantity. When Turkey import these products the tax level of those originated from EU and EFTA is lower than other countries which is applied tax. This situation is neither economic nor legal.
Keywords: Avrupa ekonomik topluluğu